MOTORCYCLE PARKING CAPACITY ANALYSIS AROUND UNIKOM CAMPUS, JALAN DIPATIUKUR, BANDUNG CITY - Sulistyarso, Wahjuadhi (Program Studi Arsitektur S-2 Universitas Pendidikan Indonesia, 2023)
The level of customer satisfaction with the quality of parking services is viewed from five aspects, namely tangible, reliability, responsiveness, assurance, and empathy. The survey method in the field (field research) is direct observation around UNIKOM BANDUNG CAMPUS through the deployment of surveyors at observation points (cordon count). The survey results were analyzed using the Microsoft Excel program. Data collection by recording the number of motorized vehicles entering and exiting at a certain time. The parking capacity for use in calculating the parking capacity survey (existing) is 176 SRP for motorbike parking in place A and 186 SRP for motorbike parking in place B. The results show that the maximum volume of parking reaches 188 motorbikes for parking A and 190 motorbikes for parking B. The highest accumulation reached 190 motorbikes for motorcycle A parking and 305 motorbikes for parking B. The use of parking space in terms of Parking Turn Over reached an average of 0.964 for parking A and 1.416 for parking B. If the need for parking space is greater than the available capacity then the number of parking spaces is not sufficient. And vice versa, if the need for parking space is less than the available capacity, it means that the number of parking spaces is still able to accommodate the vehicle that will be parked.